2020
DOI: 10.3389/fnins.2020.00672
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Hormone (CRH) Gene Family Duplications in Lampreys Correlate With Two Early Vertebrate Genome Doublings

Abstract: The ancestor of gnathostomes (jawed vertebrates) is generally considered to have undergone two rounds of whole genome duplication (WGD). The timing of these WGD events relative to the divergence of the closest relatives of the gnathostomes, the cyclostomes, has remained contentious. Lampreys and hagfishes are extant cyclostomes whose gene families can shed light on the relationship between the WGDs and the cyclostome-gnathostome divergence. Previously, we have characterized in detail the evolution of the gnath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 63 publications
(106 reference statements)
1
31
0
2
Order By: Relevance
“…The evolution of vertebrates was preceded by two successive major genome tetraploidization events 1R and 2R ( 57 , 58 ) which contributed to increase gene diversity and genome complexity. These genome duplication events occurred very early at the vertebrate origin and most likely before the cyclostome-gnathostome divergence ( 59 61 ). Our phylogenetic and gene neighborhood analysis suggests the fish c3 genes shared a common ancestral origin with the human and other tetrapod genes.…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of vertebrates was preceded by two successive major genome tetraploidization events 1R and 2R ( 57 , 58 ) which contributed to increase gene diversity and genome complexity. These genome duplication events occurred very early at the vertebrate origin and most likely before the cyclostome-gnathostome divergence ( 59 61 ). Our phylogenetic and gene neighborhood analysis suggests the fish c3 genes shared a common ancestral origin with the human and other tetrapod genes.…”
Section: Discussionmentioning
confidence: 99%
“…The CRH system possibly appeared early in metazoan evolution because homologue CRH-like peptides, CRH receptors and the CRHBP have been found both in invertebrates and vertebrates (see Lovejoy and Lannoy, 2013; Cai et al, 2021). In vertebrates, the CRH-family genes are widely distributed along the nervous system in all studied species (Cardoso et al, 2016, 2020). Initial studies in the sea lamprey Petromyzon marinus revealed the existence of a CRH system with three CRH family members [named as CRH, urotensin I (UI) and urocortin 3 (Ucn3)], two types of CRH receptors (named alpha and beta) and a single CRHBP (Endsin, 2013; Endsin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Cardoso and coworkers (2020) reported the presence of five CRH-family members in the sea lamprey [named CRH/UCNa (corresponds to CRH of Endsin et al, 2017), CRH/UCNb (corresponds to UI of Endsin et al 2017), CRH/UCNc, UCNa (corresponds to Ucn3 of Endsin et al, 2017 and Sobrido-Cameán et al, 2021a), and UCNb]. Although Cardoso et al (2020) could not infer clear orthology relationships with all gnathostome members of the CRH family in their phylogenetic and synteny analyses, CRH of Endsin et al (2017)/CRH/UCNa of Cardoso et al (2020) corresponds to the gnathostome CRH1 (Endsin et al 2017; Cardoso et al, 2020). The pattern of expression of Ucn3 (UCNa of Cardoso et al, 2020) in the sea lamprey brain was recently reported by means of in situ hybridization (ISH) by our group (Sobrido-Cameán et al, 2021a), but the brain/spinal cord distribution of the other members of the CRH system is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The sea lamprey sequences of urotensin I and Ucn3 were identified more recently [9]. Recently, the five CRH-family genes were identified (Crh1, Crh2, Ucn1, Ucn2 and Ucn3) in genomes of two lamprey species (Petromyzon marinus and Lethenteron camtschaticum; [26]). However, the expression of these genes in specific regions of the lamprey brain is not known.…”
Section: Introductionmentioning
confidence: 99%